The Role of Nigeria Traditional Costumes in Cultural Heritage Preservation: A holistic study - Babatunde Covenant Olugbenga; Deborah Adedeji; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2025)
Traditional Nigerian costumes are vital to the nation’s cultural heritage, embodying history, identity, and artistic expression. This study explores their role in cultural preservation, focusing on rituals, festivals, identity formation, and education. It examines textiles, embroidery, and symbolic attire from major ethnic groups in Nigeria, including the Yoruba’s Aso-Oke, the Igbo’s George wrapper and Ishi Agu, and the Hausa-Fulani’s Babban Riga. Using a qualitative approach, the study employs ethnographic fieldwork, interviews with cultural custodians, and a review of Nike Arts Gallery’s tie and dye techniques. Findings indicate that traditional costumes are more than decorative; they symbolize cultural identity, social hierarchy, and historical continuity. However, modernization, globalization, and mass production threaten indigenous textile-making and costume traditions. Museum exhibitions, educational programs, and collaborations with the fashion industry have emerged as effective preservation strategies. The study concludes that sustaining traditional Nigerian costumes requires a holistic approach, incorporating digital archiving, policy reinforcement, community engagement, and modern adaptations. Enhancing public awareness and supporting local artisans through sustainable initiatives will ensure the survival of these cultural symbols for future generations.